Sex-Specific Protection of Osteoarthritis by Deleting Cartilage Acid Protein 1 - Ge, Xianpeng; Ritter, Susan Y.; Tsang, Kelly; Shi, Ruirui; Takei, Kohtaro; Aliprantis, Antonios O. (PloS one, 2016)
Cartilage acidic protein 1 (CRTAC1) was recently identified as an elevated protein in the synovial fluid of patients with osteoarthritis (OA) by a proteomic analysis. This gene is also upregulated in both human and mouse OA by transcriptomic analysis. The objective of this study was to characterize the expression and function of CRTAC1 in OA. Here, we first confirm the increase of CRTAC1 in cartilage biopsies from OA patients undergoing joint replacement by real-time PCR and immunohistochemistry. Furthermore, we report that proinflammatory cytokines interleukin-1beta and tumor necrosis factor alpha upregulate CRTAC1 expression in primary human articular chondrocytes and synovial fibroblasts. Genetic deletion of Crtac1 in mice significantly inhibited cartilage degradation, osteophyte formation and gait abnormalities of post-traumatic OA in female, but not male, animals undergoing the destabilization of medial meniscus (DMM) surgery. Taken together, CRTAC1 is upregulated in the osteoarthritic joint and directly induced in chondrocytes and synovial fibroblasts by pro-inflammatory cytokines. This molecule is necessary for the progression of OA in female mice after DMM surgery and thus represents a potential therapy for this prevalent disease, especially for women who demonstrate higher rates and more severe OA.